Ethical Contestation in Law Enforcement: Reactualizing Islamic Values within Indonesia’s Rule of Law Framework. - Muhammad Taufik; Muhammad Zainal Abidin; Elsayed Amin; Rusfian Effendi (Universitas Islam Negeri Antasari Banjarmasin, 2025)
Violations of ethical values have become a common phenomenon that occurs in law enforcement in Indonesia nowadays. Violations of ethical values have become a topic of discussion and debate in the public space, with society discussing the weak law enforcement and the difficulty of getting justice. The purpose of this research is to analyze the contestation of ethical values in law enforcement by reactivating Islamic values to achieve the supremacy of law. Academically, this research is important because it reinforces the ethical theory that states that the right action aligns with moral norms. In this case, law enforcement must be carried out, as it is a shared duty and responsibility. Meanwhile, in practice, violations of ethical values in law enforcement become a serious moral issue. This research uses a qualitative approach with in-depth exploration, digging into data scattered across the internet and online news. The research findings indicate that the public debate about ethics and the weak enforcement of the law has become commonplace. Moreover, ethical values must be applied in law enforcement, so as not to trigger debates and discussions about how justice and ethics should be realized. The conclusion of this study emphasizes that the contestation of ethical values in law enforcement can be achieved by reactivating Islamic values to realize the supremacy of the law. Based on these findings, this study suggests the need for continuous training in law enforcement to create a just society. Additionally, the public should be given space to have their opinions heard to improve law enforcement in the future.